Optimizing the Implementation of Digital Rights Management to Strengthen Copyright Protection in Digital Streaming Services in Indonesia - Rifa Elvaretta Khansa; Tasya Safiranita (Dinasti Research, 2025)
The rapid advancement of digital technology has significantly heightened the risk of copyright infringement in streaming services, making the implementation of Digital Rights Management (DRM) an essential mechanism for protection. This study aims to analyze the effectiveness of DRM regulations in safeguarding copyrights on digital platforms in Indonesia and to propose measures to enhance their enforcement. The research employs a normative juridical approach, focusing on an in-depth examination of Indonesia’s Law No. 28 of 2014 on Copyright, alongside a comparative analysis of international cybersecurity regulations, particularly in the European Union (EU) and the United States (US), where DRM frameworks are more robust and extensively enforced. The findings of this study indicate that, first, while DRM is legally recognized in Indonesian regulations, its practical implementation remains vulnerable to cyberattacks and digital piracy. The existing legal framework remains general and lacks specificity in addressing the technical complexities of DRM protection for digital content. Second, comparative insights reveal that countries with more developed cybersecurity infrastructures, such as the EU and the US, provide more comprehensive protection through detailed legal frameworks and advanced technological measures that reinforce DRM enforcement. Based on these findings, this study recommends updating Indonesia’s DRM regulations, strengthening cybersecurity infrastructure by adopting international best practices, and enhancing global cooperation to combat digital piracy through cross-border networks. These measures are essential to fortifying copyright protection in Indonesia’s digital streaming landscape and ensuring a secure and sustainable digital economy.